Carbon sequestration of steel slag and carbonation for activating RO phase - Chen, Zhimin; Li, Rui; Zheng, Xianming; Liu, Jiaxiang (Cement and concrete research, 2021)
Carbonation of Ca/Mg minerals in industrial alkaline residues is a technology to sequester CO2 and reduce its emissions to the atmosphere. In this work, BSE-EDS were used to determine the mineral phase in steel slag; compositions of RO phase were identified and simulated. The carbon sequestration of steel slag was studied, and RO phase was activated by carbonation. Result shows that the amount of CO2 sequestered in steel slag and RO phase increases as carbonation time increases. Under autoclaving condition, the hydration ratio of MgO in RO phase was 20.10%. Through carbonation, up to 58.83% of MgO in RO phase can be converted into MgCO3, and the activation of RO phase by carbonation was manifested. The mechanical properties and volume stability of carbonated steel slag were improved, proving that the positive effect of carbonation on steel slag when applied in cement and cementitious materials.